Steppe lemmings and Chinese hamsters as new potential animal models for the study of the Leishmania subgenus Mundinia (Kinetoplastida: Trypanosomatidae) - Becvar, Tomas; Vojtkova, Barbora; Pacakova, Lenka; Vomackova Kykalova, Barbora; Ticha, Lucie; Volf, Petr; Sadlova, Jovana (PLoS neglected tropical diseases, 2024)
Leishmania, the dixenous trypanosomatid parasites, are the causative agents of leishmaniasis currently divided into four subgenera: Leishmania, Viannia, Sauroleishmania, and the recently described Mundinia, consisting of six species distributed sporadically all over the world infecting humans and/or animals. These parasites infect various mammalian species and also cause serious human diseases, but their reservoirs are unknown. Thus, adequate laboratory models are needed to enable proper research of Mundinia parasites. In this complex study, we compared experimental infections of five Mundinia species (L. enriettii, L. macropodum, L. chancei, L. orientalis, and four strains of L. martiniquensis) in three rodent species: BALB/c mouse, Chinese hamster (Cricetulus griseus) and steppe lemming (Lagurus lagurus). Culture-derived parasites were inoculated intradermally into the ear pinnae and progress of infection was monitored for 20 weeks, when the tissues and organs of animals were screened for the presence and quantity of Leishmania. Xenodiagnoses with Phlebotomus duboscqi were performed at weeks 5, 10, 15 and 20 post-infection to test the infectiousness of the animals throughout the experiment. BALB/c mice showed no signs of infection and were not infectious to sand flies, while Chinese hamsters and steppe lemmings proved susceptible to all five species of Mundinia tested, showing a wide spectrum of disease signs ranging from asymptomatic to visceral. Mundinia induced significantly higher infection rates in steppe lemmings compared to Chinese hamsters, and consequently steppe lemmings were more infectious to sand flies: In all groups tested, they were infectious from the 5th to the 20th week post infection. In conclusion, we identified two rodent species, Chinese hamster (Cricetulus griseus) and steppe lemming (Lagurus lagurus), as candidates for laboratory models for Mundinia allowing detailed studies of these enigmatic parasites. Furthermore, the long-term survival of all Mundinia species in steppe lemmings and their infectiousness to vectors support the hypothesis that some rodents have the potential to serve as reservoir hosts for Mundinia.
Keywords: Mice; Cricetulus; Cricetinae; Female; Leishmania; křečci praví; Leishmaniasis; Animals; ženské pohlaví; myši inbrední BALB C; leishmanióza; Disease Models, Animal; Arvicolinae; zvířata; myši; Mice, Inbred BALB C; modely nemocí na zvířatech